UPAYA AUSTRALIA UNTUK MENGHADAPI KEBIJAKAN BELT AND ROAD INITIATIVE (BRI) TIONGKOK DI PAPUA NUGINI - Nurfadhillah, Nofira; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Papua New Guinea (PNG) holds a strategic position in the South Pacific and has become a focal point in the geopolitical competition between major powers such as Australia and China. Through the Belt and Road Initiative (BRI), China has invested billions of dollars in infrastructure development across PNG, including ports, roads, power plants, and telecommunications networks. This growing presence has raised concerns in Australia, a traditional partner of PNG, which views China’s involvement as a threat to regional stability and its long-standing influence in the Pacific. This study aims to explore Australia’s efforts in responding to China's increasing influence in PNG through BRI. This study applies a qualitative research method, relying on secondary data gathered from official documents, academic journals, and news sources. The analytical framework is based on the Copenhagen School’s securitization theory, developed by Barry Buzan, Ole Wæver, and Jaap de Wilde, which sees security threats as socially constructed through discourse. The research examines how Australia constructs China's involvement in PNG as a strategic threat to its national interests. The level of analysis used is the nation-state, focusing on how domestic and international factors shape Australia’s foreign policy in the face of China’s geopolitical expansion. The findings reveal that Australia has securitized China’s BRI activities in PNG through official rhetoric, media narratives, and intelligence reports that portray BRI as a threat to national security and regional stability. In response, Australia has taken extraordinary measures, including enhancing defense cooperation with PNG, providing competitive infrastructure aid through the Australian Infrastructure Financing Facility for the Pacific (AIFFP), and strengthening its role in regional forums like the Pacific Islands Forum (PIF). These strategies reflect a shift in Australia's foreign policy from reactive diplomacy to proactive strategic engagement aimed at maintaining its dominance in the South Pacific amid China’s rise. Keywords: Threats, Belt and Road Initiative, Regional Security, Polic